Working women, caring men, and the family bank: Ideal gender relations after the Washington Consensus dans Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (Developing partnerships: gender, sexuality, and the reformed World Bank, 2009)
A critique of how the World Bank encourages gender norms, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations. By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world’s most influential development institution.
Section: xxxiv, 292 pages : illustrations
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; inégalités; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences de la gestion; sud global; systèmes d'oppressions; thématiques; économie